A multinational observational study assessing insulin use: Understanding the determinants associated with progression of therapy. Issue 5 (24th January 2019) - Ray, Kausik K.; Kendall, David M.; Zhao, Zhenxiang; Peng, Xiaomei; Caballero, A. Enrique; Polonsky, William H.; Nordstrom, Beth L.; Fan, Ludi; Curtis, Bradley H.; Davies, Melanie J.
Abstract : Aims: To describe global patterns of insulin treatment and to assess the impact of patient, provider, health system and economic influences on treatment decisions for patients with insulin‐treated type 2 diabetes (T2D). Methods: This prospective cohort study of insulin‐treated patients with T2D was conducted across 18 countries categorized as high, upper‐middle or lower‐middle income regions. Information collected from patients included knowledge of diabetes, experiences and interactions with their healthcare provider. Physician information included specialty, practice size, availability of diabetes support services, volume of diabetes patients treated and time spent per patient. Physicians determined an individualized haemoglobin A1c (HbA1c) target for each patient by the start of the study. Changes in T2D therapies and HbA1c were recorded for 2 years. Results: Complete treatment data were available for 2528 patients. Median age was 61 years and median duration of diabetes was 11.4 years. Changes to treatment regimen occurred in 90.0% of patients, but changes were less common in countries with a higher economic status ( P  < 0.001). Most treatment changes involved insulin, with changes in dose the most common. Overall predictors of change in insulin therapy included younger age, use of any insulin regimen other than basal only, higher mean baseline HbA1c and longer duration of T2D. HbA1c levels remained constant regardless of regional economic status. At baseline, 20.6% of patients were at their HbA1c target; at 2 years this was 26.8%. Conclusions: Among insulin‐treated patients with T2D, treatment changes were common; however, only approximately one‐fourth of individuals achieved their HbA1c target.